Formulasi dan Uji Sifat Fisik Patch Transdermal Ekstrak Etanol Daun Binahong (Anredera cardifolia (Tenore) Steenis) Dengan Matriks HPMC - PVP: Formulation and Physical Test of Transdermal Patch of Binahong (Anredera cardifolia (Tenore) Steenis) Ethanol Extract with HPMC - PVP Matrix - Nur Ismiyati (Politeknik Kesehatan Bhakti Setya Indonesia, 2019)
Infectious diseases and skin disorders that are harmful to human health can be caused by gram-positive bacteria, one of which is Staphylococcus aureus. One of the natural ingredients used as medicine is the binahong plant (Anredera cordifolia (Ten.) Steenis). In order to develop traditional medicinal preparations, further research is needed in the form of transdermal patches with a combination of HPMC (Hydroxy Propyl Methyl Cellulose) and PVP (Poly Vinyl Pyrolidone) polymers. Furthermore, the formulation of the best transdermal patch was tested for antibacterial activity against Staphylococcus aureus bacteria. The ethanol extract of binahong leaves was obtained by maceration method using 70% ethanol as solvent. The formulation of the transdermal patch preparation was made with three formulations with a combination of HPMC: PVP, namely 1:3 (F1) , 1:1 (F2), and 3:1 (F3). Evaluation of the physical properties of the transdermal patch consisted of a weight uniformity test, a thickness test, and a crease resistance test. The best transdermal patch was then tested for antibacterial activity. The antibacterial activity test of the transdermal patch formulation was carried out using the disc diffusion method (Kriby & Banner test) against Staphylococcus aureus bacteria. The test results show that the best formula is formula 2 with a ratio of HPMC and PVP of 1:1. The formula shows a smooth elastic patch surface, the patch thickness meets the uniformity requirements, namely CV <2% and is resistant to creases